The Communists : the story of power and lost illusions: 1948 - 1991 - Ulam, Adam B., 1922-2000 08.04.1922-28.03.2000 (A Robert Stewart book, 1992)
The story of the rise and fall of the Communists is unparalleled in modern history. After reaching the heights of power, and, at one time, ruling over one third of mankind, Communism lies in absolute shambles, the victim of the complete bankruptcy of the theory and praxis underlying the Soviet system itself. Adam B. Ulam's extraordinary new book recounts the saga of what led to this demise, starting with the postwar period of 1948 up until 1991, when the USSR cracked asunder and came to its last gasp. The Communists is a stunning reconstruction that includes a reconsideration of Stalin's notion of Communism as an instrument of his own power. There is also a penetrating analysis--often missed by most historians--of the cult of Tito, who, as "the first heretic," played a critical role in challenging the Soviet Union and holding Stalin at bay